Effects of Combined Cataract Surgery on Outcomes of Descemet's Membrane Endothelial Keratoplasty: A Systematic Review and Meta-Analysis - Kai Yuan Tey; Kai Yuan Tey; Sarah Yingli Tan; Darren S. J. Ting; Darren S. J. Ting; Jodhbir S. Mehta; Jodhbir S. Mehta; Jodhbir S. Mehta; Marcus Ang; Marcus Ang; Marcus Ang (Frontiers in Medicine, 2022)
ObjectiveA systematic review and meta-analysis of literature-to-date regarding the effects of combined cataract surgery on outcomes of DMEK.MethodsMultiple electronic databases were searched, including Cochrane Library databases, PubMed, Web of Science, and ClinicalTrials.gov. The final search was updated on 10th February 2022. We included randomized controlled trials (RCTs), non-randomized studies and large case series (≥25 eyes) of DMEK (pseudophakic/phakic) and “triple DMEK”. A total of 36 studies were included in this study. Meta-analyses were done with risk differences (RD) computed for dichotomous data and the mean difference (MD) for continuous data via random-effects model. Primary outcome measure: postoperative re-bubbling rate; secondary outcome measures: complete/partial graft detachment rate, best-corrected visual acuity (BCVA), endothelial cell loss (ECL), primary graft failure, and cystoid macular edema (CMO).ResultsA total of 11,401 eyes were included in this review. Based on non-randomized studies, triple DMEK demonstrated a better BCVA at 1-month postoperative than DMEK alone (MD 0.10 logMAR; 95% CI: 0.07–0.13; p < 0.001), though not statistically significant at 3–6 months postoperative (MD 0.07 logMAR; 95% CI: −0.01 to 0.15; p = 0.08). There was no significant difference in rebubbling, ECL, graft failures, and CMO postoperatively between the two groups (p = 0.07, p = 0.40, 0.06, and 0.54 respectively).ConclusionOur review suggests that DMEK has a similar post-operative complication risk compared to “triple DMEK” (low-quality evidence), with comparable visual outcome and graft survival rate at 6 months postoperative. High-quality RCTs specifically studying the outcomes of combined vs. staged DMEK are still warranted.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020173760, identifier: CRD42020173760.